-9(x+3)+3x+6=5x+9

Simple and best practice solution for -9(x+3)+3x+6=5x+9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9(x+3)+3x+6=5x+9 equation:


Simplifying
-9(x + 3) + 3x + 6 = 5x + 9

Reorder the terms:
-9(3 + x) + 3x + 6 = 5x + 9
(3 * -9 + x * -9) + 3x + 6 = 5x + 9
(-27 + -9x) + 3x + 6 = 5x + 9

Reorder the terms:
-27 + 6 + -9x + 3x = 5x + 9

Combine like terms: -27 + 6 = -21
-21 + -9x + 3x = 5x + 9

Combine like terms: -9x + 3x = -6x
-21 + -6x = 5x + 9

Reorder the terms:
-21 + -6x = 9 + 5x

Solving
-21 + -6x = 9 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
-21 + -6x + -5x = 9 + 5x + -5x

Combine like terms: -6x + -5x = -11x
-21 + -11x = 9 + 5x + -5x

Combine like terms: 5x + -5x = 0
-21 + -11x = 9 + 0
-21 + -11x = 9

Add '21' to each side of the equation.
-21 + 21 + -11x = 9 + 21

Combine like terms: -21 + 21 = 0
0 + -11x = 9 + 21
-11x = 9 + 21

Combine like terms: 9 + 21 = 30
-11x = 30

Divide each side by '-11'.
x = -2.727272727

Simplifying
x = -2.727272727

See similar equations:

| 6.75t+7=15.5t+14 | | 4568b-4=7 | | -v+2=3 | | 116=-4(-4y)-9(2y)+y | | (w*3-9)+(w+4)=(w*3-9)+(w+4) | | 2x+3y=5.13 | | 16+b^2+6b=0 | | 4y^6(y^2+9y+2)= | | 8n^2-3n-16=24 | | -10+3x=-4 | | X+y=y+x+200 | | 57=3v+3 | | 89-116=-4(-4y)-9(2y) | | 4x+6+6x=36 | | x+y+z=2000zxy | | (7x-4x)=y | | -5x-2=-2x-17 | | 0.5(2n-10)=22 | | -4x+5+6x=37 | | 183=3+10x | | 20+x*-4=44 | | 12x-10=8x | | 15n=6+25 | | 15n=6+255 | | 7p-2r-6r-2p= | | 5-7m=5 | | 2(3y+6)=2y+4 | | 6=4(3x+12)+13x | | 17-(2m+7)=5+4m-13 | | 4y^8+36y^7+8y^6= | | 5n+19=20 | | Z^3+3z^2-25z-75=0 |

Equations solver categories